1990
DOI: 10.1164/ajrccm/142.6_pt_1.1344
|View full text |Cite
|
Sign up to set email alerts
|

The South Karelia Air Pollution Study: The Effects of Malodorous Sulfur Compounds from Pulp Mills on Respiratory and Other Symptoms

Abstract: The paper mills in South Karelia, the southeast part of Finland, are responsible for releasing a substantial amount of malodorous sulfur compounds such as hydrogen sulfide (H2S), methyl mercaptan (CH3SH), and methyl sulfides [(CH3)2S and (CH3)2S2], into ambient air. In the most polluted residential area the annual mean concentrations of hydrogen sulfide and methyl mercaptan are estimated to be 8 and 2 to 5 micrograms/m3 and the highest daily average concentration 100 and 50 micrograms/m3. The annual mean and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 0 publications
1
32
0
2
Order By: Relevance
“…Very little is known about the role of H 2 S in modulating pain. Anecdotal evidence suggests that H 2 S may have a pronociceptive effect by causing irritation of mucosal surfaces, such as the eye and airways (11,25). Here, it was found that local administration of Na 2 S had no discernible effect on knee joint pain, as measured by hindlimb incapacitance and von Frey hair algesiometry.…”
Section: Discussionmentioning
confidence: 74%
“…Very little is known about the role of H 2 S in modulating pain. Anecdotal evidence suggests that H 2 S may have a pronociceptive effect by causing irritation of mucosal surfaces, such as the eye and airways (11,25). Here, it was found that local administration of Na 2 S had no discernible effect on knee joint pain, as measured by hindlimb incapacitance and von Frey hair algesiometry.…”
Section: Discussionmentioning
confidence: 74%
“…A self-administered questionnaire, modified from the International Study of Asthma and Allergies in Childhood (ISAAC Phase One, core questionnaire for wheezing and asthma, rhinitis and eczema; [17]) questionnaire and two previous Finnish questionnaires [18,19], was distributed by schoolteachers to 1,400 schoolchildren 7-16 years of age. The core questions for 13-and 14-year olds for wheezing and asthma, rhinitis and eczema were used unchanged (ISAAC Phase One), but some additional questions were also included from the protocol of ISAAC Phase Two and Three and the Finnish questionnaires.…”
Section: Questionnairementioning
confidence: 99%
“…The core questions for 13-and 14-year olds for wheezing and asthma, rhinitis and eczema were used unchanged (ISAAC Phase One), but some additional questions were also included from the protocol of ISAAC Phase Two and Three and the Finnish questionnaires. These questionnaires have been tested and validated [17][18][19][20]. Teachers, parents and school children were given oral and written instructions about distributing and filling in the Fig.…”
Section: Questionnairementioning
confidence: 99%
“…In studies of subjects exposed to H 2 S or TRS, researchers have identified respiratory symptoms, decreased pulmonary function test results, and increases in pulmonary disease. The groups studied were sewer workers (Richardson, 1995), oil and gas workers (Hessel et al, 1997;Mostaghni et al, 2000), and general populations (Dales et al, 1989;Jaakkola et al, 1990;Partti-Pellinen et al, 1996;Legator et al, 2001).…”
Section: Introductionmentioning
confidence: 99%